Участь шляхти в обороні Сяноцької землі під час воєнної кампанії Дьєрдя ІІ Ракоці та його союзників у січні–липні 1657 р. - Лисейко, Я. В. (Видавництво Львівської політехніки, 2014)
Вивчається перебіг подій, пов’язаних із вторгненням у Сяноцьку землю в лютому 1657 р. військ трансільванського князя Д. Ракоці та участь в обороні краю шляхти і місцевого населення. The article examines the events related to the invasion on Syanok land by Transylvanian duke D. Rakots and the participation of nobility and local population in the defense of their lands in February of 1657. Despite the fact that Sanock nobility has been informed about the invasion of D. Rakots’s army in advance, they failed to provide adequate resistance to the troops of the duke. The exception was a small clash with Mtkola Vapovsky’s cavalry troop and defense of Krosno town. When Sanock nobility faced with the enemy army, which highly exceeded the mobilization capabilities of the local region, who in its turn preferred to wait out that anxious moment. On the other hand, the D. Rakots, who was claiming the Polish crown, initially tried to keep the loyalty of the local gentry. The situation changed after the union of D. Rakots’s army with A. Zhdanovych’s Cossack corps. A wave of robbers, destruction and violence that spread through the villages and towns of Sanock land completely changed the attitude of the local population not in a favor with Transylvanian duke. Encouraged by failures of D. Rakots’s campaign and his allies, Sanock nobility started active preparation to resist the forces of Transylvanian duke that were returning from an unsuccessful campaign. However Sanock nobility showed rather passive position on its military participation in operations directly within the Polish army, by referring to the threat of Sanock land and prefering to stay closer to their homes.
Keywords: шляхта; війська; Сяноцька земля; князь Д. Ракоці; nobility; Polish army; Syanok land; duke D. Rakots